TESTING OF HUMIC LAYER NPK FERTILIZER TO PRODUCTION OF CHILI RAWIT (Capsicum frutescens L.) - Widiwurjani Widiwurjana; Makhziah Makhziah; Dyah Pramesti Kusumaningtyas (Universitas Islam Kadiri, 2021)
Cayenne pepper (Capsicum frutescens L.) is a superior commodity with high economic value. Based on data from the ministry of agriculture (2019), the productivity of cayenne pepper in East Java Province in 2018 decreased from the previous year, namely 339,000 tons to 10,147 tons. One of the reasons is the continuous use of inorganic fertilizers with increasing doses so that the soil is hard and poisonous. Increasing the efficiency of fertilization can be done by adding humic acid in the fertilization process. Humic acid is a type of organic material that has been decomposed and has stable properties, thus improving the soil fertility status, both chemical, biological, and physical properties of the soil. This condition can increase the ability of the soil to absorb and provide plant nutrients. The research was carried out at the Faculty of Agriculture UPN East Java, December 2019 to May 2020. The materials used were Maruti's cayenne pepper, planting media, manure and NPK fertilizer (16:16:16) without humic layers and NPK humic layers. The doses tested were 10, 20, 30 and 40 grams of planting both NPK and NPK humate layers, given in stages 4 times. The observation parameters were the number of productive branches, the number of periodic fruits and the total and the weight of periodic and total fruits. Using analysis of variance (ANOVA) and continued with the Least Significant Difference test with a level of 5% (BNT0.05). The results obtained were that increasing the NPK dose without humic coating would increase the production parameters to a dose of 30 grams then decreased at a dose of 40 grams. The use of humate-coated NPK showed an increase in production up to a dose of 40 g. Giving humic layer at a dose of 40 gr gave an increase in the number of fruit by 10% and fruit weight by 25% compared to without a humic layer at a dose of 30 gr. The application of humic coating on NPK fertilizer at doses of 10 and 20 gr was not significantly different from that without humate.